Amine-functionalized silica particles with magnetic core as magnetically removable adsorbents of Ag(I) ions - Karolina Gdula; Ewa Skwarek; Andrzej Dąbrowski; Inna V Melnyk (Adsorption Science & Technology)
Adsorption of silver ions over amine-functionalized silica particles with magnetic core has been studied. This adsorbent has been synthesized via sol–gel method, in the presence of Fe 3 O 4 particles as magnetic cores. As a comparison, magnetic silica adsorbent with non-functionalized surface was also synthesized. As-obtained materials have been characterized by elemental analysis, acid–base titration, nitrogen sorption measurements, X-ray photoelectron spectroscopy and scanning electron microscopy. What is more, parameters of electrical double layer at the silica adsorbent/electrolyte solution interface were also examined. Kinetic of adsorption and isotherms of silver ions were determined. The obtained adsorption of Ag(I) ions for the studied materials was in the range of about 0.2–0.3 mmol/g.